Weryfikacja modelu wyceny kapitału CAPM – na przykładzie indeksów giełdowych krajów Europy Środkowo-Wschodniej - Markowski, Lesław (Przegląd Wschodnioeuropejski, 2024)
The stock exchanges of CEE countries constitute a minor part of the capital of the entire Europe, but they are dynamically developing and cooperating capital markets. After 30 years of development, it seems reasonable whether the processes of asset pricing in them are aimed at the efficiency level of developed markets and are subject to the postulates of pricing models, such as CAPM. The work aims to test the standard CAPM using the CEE country indices. Apart from the classical approach, conditional regressions in relation to the global market condition are an important contribution to the research. The obtained results indicate that the significance of the risk premium, largely depends on the sign of the market returns, showing the advantage of conditional relations over unconditional ones. The research analyzed the sensitivity of the results to the existing socio-political crises and assessed the risk of selected stock exchanges.